The Right to Food, Land and Democracy: An Analysis From a Grassroots Perspective in Three Semi-Arid Rural Districts in Tanzania (Nordic Journal of African Studies, 2002)
This paper shows how changes in the policy environment associated with economic reforms have undermined rural food security and increased poverty among the grassroots poor in three research districts in Tanzania. It demonstrates how smallholder producers no longer have access to key support systems such as producer goods subsidies, minimum producer prices, and soft loans. It also shows how smallholder farming and livestock-keeping has become a part-time activity for many women and men, who are forced to seek additional cash incomes from off-farm activities. This reduces the amount of time available to farming and processing of food, thus undermining food security at the household level. The struggles over land, markets and other key resources between large scale investors and small scale producers, both cultivators and livestock-keepers, men and women, are emphasised.